Survey on Advances in Broadband Signal Generation and Processing of ASIC Semiconductors for Defense Satellites - Bo-Hyun Shim; Yong-Jae Yu; Kyoung-Min Song (Journal of Electromagnetic Engineering and Science)
To replace the field-programmable gate array semiconductors used in the defense satellite industry, we conducted a technical investigation of application-specific integrated circuit (ASIC) semiconductors. The analysis results show that ASIC semiconductors have the heat dissipation, reliability, and radiation resistance capabilities required in a space environment and excellent performance indicators related to the resolution of synthetic aperture radar payloads, such as operating frequency. Research and development of mission-customized ASIC semiconductors that fit the requirements for NSP(new-space paradigm) should be preceded to expanse bases of the space industry, national security capabilities for next-generation space deveolpment also to secure competitiveness of technology and domestic supply chain as space parts itselfs.